ANALISA MOTIVASI, BUDAYA ORGANISASI, DAN KOMPENSASI PADA KINERJA KARYAWAN - Sarjita, Sarjita (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
This study examines the effect of motivation, organizational cultureand compensation on employee performance. The results of motivationresearch on employee performance showed no significant, There is asignificant influence between organizational culture on employeeperformance. And there is a significant influence between the provision ofcompensation on employee performance, employee compensation programsdesigned to motivate (high morale) in their work achievement achievements.